2011
DOI: 10.1371/journal.pone.0023477
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Research on the Meaning, Ethics and Practices of Authorship across Scholarly Disciplines

Abstract: BackgroundThe purpose of this systematic review was to evaluate evidence about authorship issues and provide synthesis of research on authorship across all research fields.MethodsWe searched bibliographical databases to identify articles describing empirical quantitive or qualitative research from all scholarly fields on different aspects of authorship. Search was limited to original articles and reviews.ResultsThe final sample consisted of 123 articles reporting results from 118 studies. Most studies came for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
225
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(243 citation statements)
references
References 126 publications
(442 reference statements)
12
225
0
6
Order By: Relevance
“…Authorship is not that well understood across academia, and journal criteria for authorship can be confusing [23][24][25] . The most well known criteria for ascribing authorship in biomedical articles are those of the International Council of Medical Journal Editors, or ICMJE 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Authorship is not that well understood across academia, and journal criteria for authorship can be confusing [23][24][25] . The most well known criteria for ascribing authorship in biomedical articles are those of the International Council of Medical Journal Editors, or ICMJE 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, status, seniority, and data collection were viewed as unimportant to determining authorship. Marusic, Bosnjak, and Jeroncic (2011) conducted a systematic literature review and limited meta-analysis of research published on the issue of authorship credit. Their summary of the literature on student perspectives suggested that students put significantly higher authorship value on research tasks that are usually given to students: collection of qualitative data, data entry, statistical analyses, writing the literature review or methods sections, and total time spent.…”
Section: Student Perspectives On Authorshipmentioning
confidence: 99%
“…Marusic és mtsai [5] 123 ilyen témájú vizsgálat alapján készítettek összefoglaló cikket. A főként az orvosbiológiai és társadalomtudományi szakirodalom szerzőségi kérdéseivel foglalkozó vizsgálatokból négy olyan problémakör rajzolódik ki, amely minden szakterületen közös:…”
Section: Szerzői Szerepekunclassified